SPINAL MOBILIZATION WITH LEG MOVEMENT VERSUS TRACTION STRAIGHT LEG RAISE IN LOW BACK PAIN PATIENTS DUE TO HERNIA NUCLEUS PULPOSUS - Suharto Suharto; Sudaryanto Sudaryanto; Tiar Erawan; Muhammad Saleng (Bajang Institute, 2023)
The purpose of this study was to compare the effectiveness of Spinal Mobilization With Leg Movement (SMWLM) and Traction Straight Leg Raise (TSLR) on limited range of motion and lumbar functional impairment in herniated nucleus pulposus patients. The research method is an experiment with a pre-test – post-test two group design. A total of 24 herniated nucleus pulposus patients were simply randomized into 2 groups, namely group I was given Mobilization With Leg Movement and group II was given Traction Straight Leg Raise. The results showed that the range of motion for group I obtained a value of p = 0.045 and functional lumbar with a value of p = 0.012. In group II, a value of p = 0.001 was obtained for range of motion and functional lumbar with a value of p = 0.001. The independent t-test obtained a value of p = 0.000 for range of motion and a value of p = 0.001 for lumbar functional value. Based on the findings of this study, SMWLM and TSLR have a significant effect on improving the range of motion and lumbar function in patients with herniated nucleus pulposus, but SMWLM is more effective than TSLR in increasing range of motion and lumbar function in patients with herniated nucleus pulposus